Morphological characteristics, seed quality, and seedling growth of several local rice (Oryza sativa L.) genotypes - Chyntia Cessa Salsabila Susanto; Ni Kadek Ema Sustia Dewi (Agrovigor, 2026)
Rice (Oryza sativa L.) is a major global agricultural commodity and plays a crucial role in food security, especially in Asia. The decreasing presence of local rice varieties highlights the need for conservation through identification and evaluation, as they represent valuable genetic resources for the development of superior cultivars. This study aimed to analyze differences in seed morphology, seed quality, and seedling growth among several local rice genotypes. A Completely Randomized Design (CRD) with one factor was used, involving four genotypes: Sedayu, HMS 700, Tri Sultan 05, and a control variety, Situbagendit. Each treatment was replicated six times, totaling 24 experimental units. The study was conducted in three stages: seed morphological characterization, seed quality testing, and field evaluation at the vegetative phase. Observed seed traits included grain length, width, color, presence of trichomes on lemma and palea, tip hair color, and rice color. Seed quality parameters included moisture content, purity, 1,000-grain weight, germination rate, vigor index, maximum growth potential (MGP), and growth speed index (GSI). Field observations included leaf color, plant height, and fresh and dry seedling weight. Data were analyzed using ANOVA at the 5% level, followed by Duncan’s Multiple Range Test (DMRT). The results indicated significant differences in seed morphological traits among genotypes, particularly in grain color, rice color, length, and width. The Tri Sultan 05 genotype demonstrated superior performance in germination rate, vigor index, MGP, plant height, and both fresh and dry biomass.